2014
DOI: 10.1089/apc.2013.0294
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome Among Antiretroviral-Naive and Antiretroviral-Experienced HIV-1 Infected Thai Adults

Abstract: Metabolic syndrome (MS), a group of interrelated risk factors for cardiovascular diseases (CVD) and type 2 diabetes, has been increasingly reported among HIV-infected patients. Data on the prevalence and risk factors for MS among HIV-1 infected Thai adults are limited. The study collected cross-sectional data from 580 HIV-1 infected adults-46.2% were men and 71% were antiretroviral therapy (ART)-experienced. The majority (78.8%) of them used non-nucleoside reverse transcriptase inhibitor-based regimens. Data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
50
3
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 36 publications
12
50
3
3
Order By: Relevance
“…There were 37,110 HIV-infected patients in total, with females representing approximately 28%. Thirty-one studies (61%) were conducted in low-and middleincome countries with the highest number of studies (n = 8) reported in India [22,27,29,30,45,47,59,61], followed by six studies in Nigeria [24,31,34,36,50,54], and four studies each in Brazil [23,32,41,44], Norway [15,16,55,62], and USA [17,39,40,53]. Nonetheless, studies conducted in high-income countries were generally larger in size (n = 30,120 participants), compared with studies conducted in low-and middleincome countries (n = 7488).…”
Section: Resultsmentioning
confidence: 99%
“…There were 37,110 HIV-infected patients in total, with females representing approximately 28%. Thirty-one studies (61%) were conducted in low-and middleincome countries with the highest number of studies (n = 8) reported in India [22,27,29,30,45,47,59,61], followed by six studies in Nigeria [24,31,34,36,50,54], and four studies each in Brazil [23,32,41,44], Norway [15,16,55,62], and USA [17,39,40,53]. Nonetheless, studies conducted in high-income countries were generally larger in size (n = 30,120 participants), compared with studies conducted in low-and middleincome countries (n = 7488).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 573 abstracts and 17 full texts, including seven duplicate records, were excluded, leaving 39 eligible observational studies. [5][6][7][8]15,16, Thirty of these included studies were cross-sectional surveys, 5,16,[18][19][20][21][22][23][24][25][26]28,[31][32][33][34][35][36][37][39][40][41][42][44][45][46]48,49 whereas the other nine were cohort studies. A total of 44 903 HIV-infected patients (28% females) from 21 countries were included in our analyses, with significantly more study participants from high-income countries compared with low-and middle-income countries (89% versus 11%).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] In addition, no systematic evidence has provided comprehensive estimates of the impact of ART exposure on blood pressure levels and hypertension risk. We therefore set out to address this gap in the current body of evidence by performing a systematic review and meta-analysis to compare blood pressure levels and hypertension risk between HIV-infected patients naive and exposed to ART.…”
Section: Introductionmentioning
confidence: 99%
“…The usual methods applied in the diagnosis vary from self-perception [6, 12], health professional [12] or physical examination [7], skinfolds measurements [8], or even imaging assessment such as dual emission X-ray absorptiometry (DEXA) [7, 9], CT [9], or MRI [10] for confirmation of fat distribution changes [10, 11]. Although several methods have been developed, there is no gold standard for characterization of LA and LH, or mixed forms [2, 13].…”
Section: Introductionmentioning
confidence: 99%